2005
DOI: 10.1016/j.neuroimage.2005.06.041
|View full text |Cite
|
Sign up to set email alerts
|

Neural dynamics of error processing in medial frontal cortex

Abstract: Adaptive behavior requires an organism to evaluate the outcome of its actions, such that future behavior can be adjusted accordingly and the appropriate response selected. During associative learning, the time at which such evaluative information is available changes as learning progresses, from the delivery of performance feedback early in learning to the execution of the response itself during learned performance. Here, we report a learning-dependent shift in the timing of activation in the rostral cingulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
99
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(107 citation statements)
references
References 35 publications
5
99
1
2
Order By: Relevance
“…However, although the amygdala plays a central role in the first process, other brain structures are involved in the second. Functional magnetic resonance imaging (fMRI) and ERP studies using similar paradigms to the current one have demonstrated an important role for the pMFC (including the ACC and pre-SMA ; Holroyd et al 2004 ;Mars et al 2005) and the basal ganglia Ullsperger & von Cramon, 2006) in learning from errors. Currently, the IES interpretation of PP does not include these processes and brain areas and hence does not allow for any specific predictions to be made.…”
Section: Integrationmentioning
confidence: 78%
“…However, although the amygdala plays a central role in the first process, other brain structures are involved in the second. Functional magnetic resonance imaging (fMRI) and ERP studies using similar paradigms to the current one have demonstrated an important role for the pMFC (including the ACC and pre-SMA ; Holroyd et al 2004 ;Mars et al 2005) and the basal ganglia Ullsperger & von Cramon, 2006) in learning from errors. Currently, the IES interpretation of PP does not include these processes and brain areas and hence does not allow for any specific predictions to be made.…”
Section: Integrationmentioning
confidence: 78%
“…Changes in ACC activation over time have previously been shown as a function of task practice (Milham et al, 2003), experiment duration (Erickson et al, 2004), or focus of attention (Mars et al, 2005). However they were either unrelated to the behavioral index measuring conflict (Milham et al, 2003;Erickson et al, 2004) or they were related to attentional shifts regarding the source of error information (Mars et al, 2005).…”
Section: Discussionmentioning
confidence: 91%
“…However they were either unrelated to the behavioral index measuring conflict (Milham et al, 2003;Erickson et al, 2004) or they were related to attentional shifts regarding the source of error information (Mars et al, 2005). These findings suggest that there could be changes in the neural activity without corresponding changes in behavioral measures, thus questioning the role of the ACC in conflict monitoring and subsequent control implementation.…”
Section: Discussionmentioning
confidence: 99%
“…Medial prefrontal cortex (PFC), including the anterior cingulate cortex (ACC) and supplementary motor area (SMA)/pre-SMA (Rushworth et al, , 2007, and dorsolateral PFC (DLPFC) are often found to be more active after the presentation of negative performance feedback in adults (Mars et al, 2005;Zanolie et al, 2008a). Pre-SMA/ACC is thought to signal response conflict and to predict activation in DLPFC, a region that is considered to be important for subsequent performance adjustment (Kerns et al, 2004).…”
Section: Introductionmentioning
confidence: 99%